Assessment of different carbon and salinity level on growth kinetics, lipid, and starch composition of Chlorella vulgaris SAG 211-12 - SAYAR, AHMET ALP; KAZAN, DİLEK; SAYAR, NİHAT ALPAGU (TAYLOR & FRANCIS INC, 2020)
The quality of microalgal biofuel depends on the fatty acid (FA) distribution. A high ratio of saturated fatty acids (SFAs) favors better biofuel characteristics. Palmitic acid (C16:0) and stearic acid (C18:0) are essential FAs for required biodiesel quality. In this study, combined effects of growth medium concentrations of NaCl, glucose and glycerol on cell composition and FA profile of the Chlorella vulgaris SAG 211-12 were investigated. A central composite design (CCD) based design of experiments (DoE) was used for experimental setup. According to experimental results, the maximum mass fraction for palmitic acid (C16:0), 40.67% of total fatty acids, was obtained in the medium supplemented with 0.9% (w/v) NaCl, 0.3% (w/v) glucose, and 0.3% (w/v) glycerol, whereas stearic acid (C18:0) percentage reached the highest value of 22.16% of total fatty acids in the presence of 2.5% NaCl, 0.6% glucose, and 0.6% glycerol. According to the same set of designed experiments, best starch content was found as 22.08% of dry cell weight in a medium containing 2.0% NaCl, 0.3% glucose, and 0.3% glycerol. C16:0 mass fraction as a function of three medium ingredient concentrations was modeled using a Kriging model. Optimum concentrations of NaCl, glucose and glycerol to reach maximum C16:0 fraction were predicted as 0.5, 1, and 1%, respectively.
Keywords: Microalgae; chlorella vulgaris SAG 211-12; fatty acids; starch; design of experiments; RESPONSE-SURFACE METHODOLOGY; NANNOCHLOROPSIS-OCULATA; BIODIESEL PRODUCTION; BIOMASS PRODUCTION; ENHANCED GROWTH; NACL STRESS; CELL-GROWTH; MICROALGAE; ACCUMULATION; OPTIMIZATION